Influence of Salary Reduction Due to Covid 19 Pandemic on the Economy and Health Educators’ Job Commitment in Public Secondary Schools in Delta State - I. N., Okudaye (International Journal For Research In Educational Studies, 2021)
This study was undertaken to investigate influence of salary reduction due to COVID 19 pandemic on the economy and health educators’ job commitment in public secondary schools in Delta state. The study employed descriptive survey design. The population was 1376 principals and health educators’ in public secondary schools in Delta State. The population was 463 principals and 913 health educators’ in public secondary schools in Delta State The researcher sampled 185 principals or (40% ) and 456 health educators or (50% ) in public secondary schools in Delta State. The total sample was 641. The stratified random sampling technique was used to select 40 % of principals and 50% of health educators that were utilized in the study. The instrument for the study was a questionnaire titled “Salary Reduction and Health educators’ Job Commitment Questionnaire (SRHEJCQ﴿. The instrument was validated by expert’s opinion. Out of the entire copies of 641 instruments administered, a sum of 679 copies was retrieved. 223 principals and 456 health educators. Mean rating and standard deviation were utilised to answer the three research questions. Mean rating of 2.50 was assumed as the critical level of receipt, while mean rating below 2.50 was rejected. z - test was utilised to test the three null hypotheses formulated that guided the study at 0.05 levels of significance. Findings showed that salary reduction due to COVID 19 pandemic on the economy influences negatively health educators’ job commitment in public secondary schools in Delta state was high as the ratings were high. Salary reduction due to COVID 19 pandemic on the economy influences negatively health educators’ job commitment in public secondary schools in Delta state in terms of their sex and age was high as the ratings were high. There was no significant difference on influence of salary reduction due to COVID 19 pandemic on the economy and health educators’ job commitment in public secondary schools in Delta state at 0.05 level of significance. It was concluded in the study that salary reduction due to COVID 19 pandemic on the economy influences negatively on health educators’ job commitment in public secondary schools in Delta state as well as in terms of their sex and age.